2014
DOI: 10.1186/s12865-014-0034-3
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer properties of gastropodan hemocyanins in murine model of colon carcinoma

Abstract: BackgroundVarious immunotherapeutic approaches have been used for the treatment of cancer. A number of natural compounds are designed to repair, stimulate, or enhance the immune system response. Among them are the hemocyanins (Hcs) - extracellular copper proteins isolated from different arthropod and mollusc species. Hcs are oxygen transporter molecules and normally are freely dissolved in the hemolymph of these animals. Hemocyanins are very promising class of anti-cancer therapeutics due to their immunogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 32 publications
1
49
0
1
Order By: Relevance
“…Interestingly, the three hemocyanins induced significant elevations in the mRNA levels of CD40L (Cd40lg) in macrophages, which might support the observed nonspecific antitumor activity of hemocyanins in several cancers (6,71). CD40-CD40L interactions promote the activation of NK cells by murine macrophages (72).…”
Section: Discussionmentioning
confidence: 88%
“…Interestingly, the three hemocyanins induced significant elevations in the mRNA levels of CD40L (Cd40lg) in macrophages, which might support the observed nonspecific antitumor activity of hemocyanins in several cancers (6,71). CD40-CD40L interactions promote the activation of NK cells by murine macrophages (72).…”
Section: Discussionmentioning
confidence: 88%
“…In addition, Tchorbanov et al have achieved enhanced antigen immunogenicity for the epitope of influence A virus hemagglutinin bound to RtH or its subunits and they have suggested that Hcs can be successfully used in many immunization protocols as adjuvants or protein carriers [23]. Gesheva et al have demonstrated the potential of RtH as cancer preventive vaccine, which was tested "in vivo" experiments with murine model of colon carcinoma [24].…”
Section: Introductionmentioning
confidence: 98%
“…They most likely reflect the snail‐intrinsic, reversible O ‐GalNAc glycosylations , initiating protein glycosylations even in mollusks . While the agglutinins are engaged in self‐defense, the agglutinin‐free hemocyanin from H. pomatia (HPH) exerted strong anti‐proliferative effects in murine models of colon carcinoma . In addition, Concholepas hemocyanin inhibits the growth of bladder tumors , and the Gal( β 1‐3)GalNAc‐bearing hemocyanin of Megathura crenulata (keyhole limpet hemocyanin, KLH) shows cross‐reactivity with T antigen , inducing a potent Th1‐dominant immune response and was used as an effective immunogenic carrier in dendritic cell vaccination developed for immunotherapy of human B cell lymphoma .…”
Section: Cross‐specificity Between Mammalian Anti‐a/anti‐tn/t‐reactivmentioning
confidence: 99%